Impacts of yeast Tma20/MCTS1, Tma22/DENR and Tma64/eIF2D on translation reinitiation and ribosome recycling - Jendruchová, Kristína; Gaikwad, Swati; Poncová, Kristýna; Gunišová, Stanislava; Valášek, Leoš Shivaya; Hinnebusch, Alan G (bioRxiv, 2024)
Recycling of 40S ribosomal subunits following translation termination, entailing release of deacylated tRNA and dissociation of the empty 40S subunit from mRNA, involves yeast Tma20/Tma22 heterodimer and Tma64, counterparts of mammalian MCTS1/DENR and eIF2D. MCTS1/DENR enhance reinitiation at short upstream open reading frames (uORFs) harboring penultimate codons that confer dependence on these factors in bulk 40S recycling. Tma factors, by contrast, inhibited reinitiation at particular uORFs in extracts; however, their roles at regulatory uORFs in vivo were unknown. We examined effects of eliminating Tma proteins on reinitiation at regulatory uORFs mediating translational control of GCN4 optimized for either promoting (uORF1) or preventing (uORF4) reinitiation. We found that the Tma proteins generally impede reinitiation at native uORF4 and uORF4 variants equipped with various penultimate codons regardless of their Tma-dependence in bulk recycling. The Tma factors have no effect on reinitiation at native uORF1, and equipping uORF1 with Tma-dependent penultimate codons generally did not confer Tma-dependent reinitiation; nor did converting the uORFs to AUG-stop elements. Thus, effects of the Tma proteins vary depending on the reinitiation potential of the uORF and the penultimate codon, but unlike in mammals, are not principally dictated by the Tma-dependence of the codon in bulk 40S recycling.
Keywords: reinitiation; DENR; MCTS1; eIF2D; ribosome recycling; Tma